Professoras iniciantes e as práticas da língua inglesa no cotidiano da profissão : necessidades e formação - Cardoso, Fernanda de Mello (2018)
The current study is inserted in the Graduate Program in Education of the Federal University of Mato Grosso, university campus of Rondonópolis (PPGEdu/UFMT/CUR) and bound to the project of the Observatory of Education (OBEDUC/CAPES/INEP/SECADI) which offers continuing teacher education to beginner teachers with the intention of attending their needs, aiming at alleviating their distress upon challenges and dilemmas. One of the demands pointed out by the new teachers was the lack of teacher education for the attendance to the curriculum matrix of 2011 for the primary school of the Municipal System of Rondonópolis/MT which includes English in the 1st and 2nd Cycles (1st to 5th grade). In this context, the teachers felt insecure and incapable and, therefore, requested the university for specific teacher education. Thus, within the framework of OBEDUC, a workshop of 20 hours of study on some of the contents of the curricular documents was offered to them. The aim was to investigate the meanings beginner teachers egresses of the Course of Pedagogy attribute to the learnings constructed in the workshop of study of the English language, upon the absence of knowledge on a subject whose contents they must work with the children. The research was based on the qualitative approach and for the data gathering narratives extracted from the field diaries of the researcher and the participants, as well as interviews, were utilized. The investigation subjects are two pedagogy teachers from the municipal system. For this purpose, it was questioned: what reactions manifest the beginner teachers upon the demand of work in subjects for which they did not have teacher education and preparation and were not provided with conditions by the system of education in which they serve? What meanings attribute the beginner teachers to the teacher education and preparation received and what point out the narratives about the impact of it on the practices of the English language? The results manifest that the actions promoted with the workshop of study of English contributed with the teacher education and preparation of the teachers engajed on the process as learners and professionals in search of specific knowledge, since the proposed activities met their teacher educational needs.